Microevolution of Burkholderia pseudomallei during an acute infection. - Limmathurotsakul, D; Holden, M; Coupland, P; Price, E; Chantratita, N; Wuthiekanun, V; Amornchai, P; Parkhill, J; Peacock, S (American Society for Microbiology, 2014)
We used whole-genome sequencing to evaluate 69 independent colonies of Burkholderia pseudomallei isolated from seven body sites of a patient with acute disseminated melioidosis. Fourteen closely related genotypes were found, providing evidence for the rapid in vivo diversification of B. pseudomallei after inoculation and systemic spread.